Shape-memory surfaces for cell mechanobiology. Issue 1 (18th February 2015) - Ebara, Mitsuhiro
Abstract: Shape-memory polymers (SMPs) are a new class of smart materials, which have the capability to change from a temporary shape 'A' to a memorized permanent shape 'B' upon application of an external stimulus. In recent years, SMPs have attracted much attention from basic and fundamental research to industrial and practical applications due to the cheap and efficient alternative to well-known metallic shape-memory alloys. Since the shape-memory effect in SMPs is not related to a specific material property of single polymers, the control of nanoarchitecture of polymer networks is particularly important for the smart functions of SMPs. Such nanoarchitectonic approaches have enabled us to further create shape-memory surfaces (SMSs) with tunable surface topography at nano scale. The present review aims to bring together the exciting design of SMSs and the ever-expanding range of their uses as tools to control cell functions. The goal for these endeavors is to mimic the surrounding mechanical cues of extracellular environments which have been considered as critical parameters in cell fate determination. The untapped potential of SMSs makes them one of the most exciting interfaces of materials science and cell mechanobiology.